Use of Information Technology in Teaching English - Turaeva Guzal Xursanovna; Nekboeva Ra’no Zokirovna; Avlaeva Saida Bozorovna (Research Parks Publishing LLC, 2021)
This article discusses the role and importance of using technologies in teaching English. Information technologies are the result of knowledge explosion. These include hardware and software technologies and facilitate teaching learning process. Using Information Technologies learners are now able to participate in learning communities throughout the world. They are independent and free in choice of their programmes of study and access to the resources